High-Throughput Real-Time Reverse Transcription-PCR Quantitation of Hepatitis C Virus RNA - M. Martell; Jordi Gómez; Juan Ignacio Esteban; Sílvia Sauleda; Josep Quer; Beatriz Cabot; Rafael Esteban; Jaime Guardia (1999)
ABSTRACT We describe a rapid and reproducible method for assessment of the hepatitis C virus (HCV) load in serum samples. The method combines Taqman technology (Roche) and the ABI Prism 7700 (Perkin Elmer) real-time sequence detection system. We have optimized a single-tube reverse transcription-PCR (RT-PCR) that contains a dual-labeled fluorogenic probe to quantify the 5′ noncoding region (5′ NCR) of HCV. The probe contains a fluorescent reporter at the 5′ end and a fluorescent quencher at the 3′ end. The use of such a probe combined with the 5′-3′ nuclease activity of Taq polymerase allows direct quantitation of the PCR product by the detection of a fluorescent reporter released in the course of the exponential phase of the PCR. For accurate quantitation of the number of copies of HCV in samples containing unknown quantities, we have used serial dilutions of a synthetic 5′ NCR RNA standard of HCV that was previously quantified with an isotopic tracer. The method has a 5-log dynamic range (10 3 to 10 7 ). The coefficient of regression of the standard curve was, on average, 0.98. The intra-assay and the interassay coefficients of variation of the threshold cycle were 1% and 6.2%, respectively. Seventy-nine RNA samples from the sera of infected patients were quantified by this method. Comparison of the results with those obtained by other quantitation methods (the Quantiplex 2.0 branched-DNA assay and the Superquant assay from the National Genetics Institute) revealed a significant correlation with all of the results. The mean values were also statistically comparable. In conclusion, the high sensitivity, simplicity, and reproducibility of the real-time HCV RNA quantitation which allows the screening of large numbers of samples, combined with its wide dynamic range, make this method especially suitable for monitoring of the viral load during therapy and tailoring of treatment schedules.